Domestic violence : A Huge Difference Between Statistic And The Real Picture: Understanding the Hidden Reality of Domestic Violence in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
It is a phenomena that may be seen all throughout the world, but it is most pronounced in Indiabecause of the frequency of dowry, male dominance, and joint-family systems. Consequently, thesefactors contribute to the fact that women are victims of violence in the home. Not only might womenendure violence at the hands of their husbands, but also at the hands of their husbands' family members.This is especially the case when the issue at hand is dowry, whether there is no dowry at all or an amountthat is insufficient. Few incidences are reported, which contributes to the inaccuracy of the data since it isingrained in the culture of India to be concerned about the views and opinions of others. Consequently,societal shame is also a factor. In most cases, the police and the courts are informed when the victimdies as a result of their injuries, when they commit suicide, or when they go to a hospital to seek medicaltreatment. If this is not the case, then minor forms of abuse are often hidden.